Cover Glass Strength Design for Industrial Use PCAP LCD Module. Issue 1 (June 2014) - Teramoto, Hiroshi; Morii, Yasuhiro; Mori, Akihiro; Yoshimoto, Takahiro
Abstract Recently the cover glass on LCD with touch panel has become to be used. To provide safe products against various loads in the market, it is necessary to understand the stress occurred in the glass. We developed the design method with the FEM analysis with optimized parameters based on measurement results.